Critérios de justiça distributiva em saúde - Roberto Passos Nogueira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– Different conceptions about distribution criteria in health services are discussed based on the notion of fairness, and in the assumption that health requirements are simultaneously social security needs. Issues of equity and limits in distribution of health services are highlighted as they are extracted from the history of social security in Brazil and the ideals of equality and universality of access and integrality of care pursued by Brazilian Health Movement in the 1980s, which led to the creation of Unified Health System (SUS). Along this institutional history, it is emphasized the emergence of a conflict among the social insurance, the sanitarian and the social security rationalities. The linkage between health and social security is studied through the concept of fundamental capabilities, according to Martin Heidegger's philosophy and similar concept presented by Amartya Sen. Concluding, it is stated that SUS policies should refer themselves more explicitly to the principles of social security rationality having the aim of preserving health as a fulcrum of fundamental human capabilities.
Keywords: I18; 330; Gesundheitswesen; Brasilien